Antioxidant activities of extract from Makmao seed waste - Kittipongpittaya, Ketinun; Puangploy, Premsak; Kullamethee, Piyarach; Fakkheow, Pitchaon; Kareevate, Passaporn; Philkliang, Bunyakorn (Asia-Pacific Journal of Science and Technology, 2021)
Makmao is a nutritious tropical fruit that is usually processed into products such as juice, wine, and jam. During the process, Makmao seeds are generated as a major form of waste. The aim of this research was to evaluate the antioxidant properties of Makmao seeds extracts using seed from different cultivars (Yaikumtar, Lungkumlar, and Thepnimit) with two ripeness degrees (mature and fully ripe) of Makmao fruits and using different solvents (hexane and ethanol) for extraction. The results show that the highest % yield (15.58±2.42 by weight) was obtained from fully ripe Lungkumlar seed extracted with ethanol, while the ethanol extract from fully ripe Yaikumtar seed possessed the highest content of phenolic and flavonoid. Considering the anthocyanin content, Lungkumlar seed at a fully ripe stage extracted with ethanol contained the highest amount of monomeric anthocyanin. The ethanol extract obtained from mature Yaikumtar seed showed the highest antioxidant activity determined by 2, 2-Diphenyl-1-picryl hydrazyl (DPPH), 3-ethylbenzothaia zoline-6-sulfonic acid (ABTS) and Ferric reducing antioxidant power assay (FRAP) (6.66±2.52, 7.80±2.08, and 5.84±1.07 mg TEAC/g extract, respectively) compared to the other extracts. According to the findings, the ethanolic extract from fully ripe Yaikumtar seed possessed the highest content of phenolic and flavonoid, and a relatively high antioxidant activity compared to the other extracts in this study. It could be further explored for its use as a potential natural antioxidant in the food products.